KELAYAKAN PEGAS DAUN DALAM PENERIMAAN BEBAN OPTIMAL - Daryono, D (Jurnal Teknik Industri, 2010)
Until now days a lot of vehicle still used suspension Leaf spring either in front or in rearsuspension. Commonly the this suspension consist of several peace of springs that called leafspring. This research is focus on laboratory work without experimental test. As a result onlytheoretical conclusion. Natural frequency by modal analysis show that all mode are more than100 Hz. It is very dangerous value of safety passengers and the suspension its self. But withharmonic simulation between 1 until 10 Hz input frequency will be resulted no more than 20mm amplitude. This is the range where passenger still get comfortability according to Janeway diagram of comfort ability. Consequently a lot of people or automotive engineer still usethis kind of suspension .